Localization of mercury in the kidney during experimental acute tubular necrosis studied by the cytochemical Silver Amplification method. - Hultman, P. (1986)
An intravenous injection of 3.0 mg HgCl2/kg bw was given to Balb/c mice. The concentration of mercury in the red blood cells, serum, and kidney was determined after 5 min, 30 min, 2 h and 24 h by atomic absorption spectrophotometry. The concentration of mercury in the serum showed a maximum after 5 min, and reached a constant low level after 30 min, whereas the concentration of mercury in the red blood cells gradually decreased and reached a similar low level at 24 h. The concentration of mercury in the kidney was greatest after 2 h and was markedly reduced at 24 h. The distribution of mercury in the kidney was followed for up to 17 days by the cytochemical Silver Amplification method applied at the light and electron microscopical levels. Mercury accumulated rapidly, but only in the proximal tubular epithelial cells, preferentially in the S2 and S3 segments. At the subcellular level mercury was only found in endocytic structures, and accumulated in the lysosomes. Very large mercury-containing lysosomes developed in the distal S3 segment. Cell necrosis was severest in the S2 and proximal S3 segments. Regenerated and differentiating epithelial cells in the proximal tubules still showed many mercury-containing lysosomes 17 days after the injection.